Expression pattern of OCT 4, NANOG and HSP 90 β gene in oocytes and various stages of in vitro produced sheep embryos - RAJA, S; BALASUBRAMANIAN, S; DHINAKARRAJ, G; VEERAPANDIAN, C (The Indian Journal of Animal Sciences, 2015)
The study was conducted to assess the expression pattern of pluripotent genes (OCT 4 and NANOG) and stress response gene HSP 90 ÃŸ by quantitative real time polymerase chain reaction (qRT-PCR) in immature and mature oocytes and 2 cell, 4 cell, morula stages of in vitro fertilized (IVF) and parthenogenetically activated (PA) preimplantation ovine embryos to investigate the similarity between them in turn for the establishment of embryonic stem cells (ESCs) from parthenote embryos. The pluripotent related genes showed almost similar pattern of expression between IVF and PA embryos at all the developmental stages which indicated that PA embryos could be used as an alternate source for the production of embryonic stem cells. The stress response gene showed increased levels after in vitro maturation and non significant differences between IVF and PA embryos, thus, indicating no significant differences between the quantum of stress experienced by the 2 groups of embryos which would not affect the development of embryo quality and in turn affect the parthenote embryonic stem cells (PESCs).